Confirmation bias in criminal cases - Liden, Moa (United Kingdom: Oxford University Press, 2023)
'Confirmation bias is a tendency to selectively search for and emphasize information that is consistent with a hypothesis or preferred conclusion. At the same time, opposing information is ignored or interpreted in ways that do not threaten the predetermined conclusion. Importantly, confirmation bias is a more or less subconscious phenomenon. Hence, legal actors and criminal practitioners who are expected to be objective, who may make genuine efforts to be objective and who also perceive of themselves as objective, may still display a confirmation bias. This includes police officers, crime scene investigators, forensic analysts, pathologists, prosecutors and judges and the range of distinct decision making tasks that these actors have, for example, interviews with suspects, witness, plaintiff, crime scene investigations, autopsies, decisions about whether to press charges and whether to convict. Since confirmation bias can be present at all stages of criminal investigations and proceedings, it constitutes a serious risk of error, for example, wrongful convictions and wrongful acquittals. It is therefore essential to find and use bias mitigation measures, and a good starting point is the explanations of this bias provided in cognitive, motivation and emotion, social and organizational psychology. This includes measures such as changing decision maker, contextual information management, linear sequential unmasking and structured evaluations of the evidence'--
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ CIP/ Areesh Education & Trading
Includes bibliographical references and index. (267-268 pages)